Species of Diatrypaceae associated with grapevine trunk diseases in Eastern Spain - LUQUE, Jordi; GARCIA-FIGUERES, Francesc; LEGORBURU, Francisco Javier; MURUAMENDIARAZ, Argiñe; ARMENGOL, Josep; TROUILLAS, Florent (Phytopathologia Mediterranea, 2012)
The presence and diversity of Diatrypaceae species occurring on grapevines in Eastern Spain were investigated. Several species were identified on the basis of morphological characters and phylogenetic analyses of the complete sequence of the internal transcribed spacers of the ribosomal DNA and part of the β-tubulin gene. Five species of Diatrypaceae isolated from the wood of diseased grapevines, pruning debris and/or perithecia were identified, including Anthostoma decipiens, Cryptovalsa ampelina, Eutypa lata, Eutypella citricola and Eutypella microtheca. Additionally, four taxa could not be identified to the species level but were closely related to Eutypa tetragona based on phylogenetic analyses. Eutypa lata was the most prevalent species and showed the greatest degree of genetic diversity. Cryptovalsa ampelina and E. microtheca ranked second in the frequency of isolations, while all the remaining species were less frequently isolated. Eutypella citricola and E. microtheca are reported for the first time as occurring on grapevine in Spain and this is the first report of A. decipiens occurring on grapevine.